Peningkatan Kewaspadaan Masyarakat Kelurahan Jaticempaka, Bekasi Terhadap Banjir dengan Alat Pendeteksi Banjir - Hartanto, Sri; Nurbayan; Priyono, Tri Ongko; Wiharja, Ujang; Hakim, Teten Dian; Slamet Purwo Santosa; Bayu Kusumo; Al Bahar, Abdul Kodir; Naibaho, Nurhabibah; Aditya, Lukman (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Floods occur due to rainfall that is high enough so that the water level rises above normal limits and overflows into residential areas. Floods can occur regardless of time, so there is a need to increase public awareness of floods. In the environment around the Krisnadwipayana University, namely, Jaticempaka Village, Bekasi, which is one of the public service partners, floods often occur due to the overflow of the Sunter River. Based on surveys and monitoring, the lack of public awareness of Jaticempaka Village, Bekasi, regarding flood disasters due to the lack of a system or device that can detect the high water level in the Sunter River, which causes flooding. Therefore, lecturers and students of the Electrical Engineering Study Program, Faculty of Engineering, Krisnadwipayana University were inspired to participate with carrying out public service, namely by making and installing a flood detection device that can detect water level levels at the Sunter River using an Atmega 8535 microcontroller and an ESP8266 MCU node. It is hoped that by installing the flood detection device, the public of Jaticempaka Village, Bekasi, can obtain information about the water level of the Sunter River, so that can increase public awareness of flood disasters.